An Ectopic Intrathoracic Kidney in an Adult Female: A Case Report - Tharun Ganapathy Chitrambalam; Nidhi Mariam George; Ramyasree Paladugu; Sundeep Selvamuthukumaran; Lokesh Reddy (Journal of Clinical and Diagnostic Research, 2022)
The kidney is an organ prone to congenital anomalies owing to its complex and sequential development. Ectopia of the kidney is a rare entity with intrathoracic ectopia being an exceptionally uncommon occurrence. Intrathoracic kidneys represent less than 5% of all renal ectopias with a prevalence rate of less than 0.01%. The concurrent association of an intrathoracic kidney with a Bochdalek hernia is extremely infrequent with an incidence of 0.25%. Most of the patients are asymptomatic and have an uneventful clinical course. It is often incidentally detected simulating a posterior mediastinal mass. Thoracic kidney is a condition that shows male predominance. Here, authors present a case of a 43-year-old female patient who presented to the Institution with breathlessness and associated chest pain. Computed Tomography (CT) scan revealed left-sided Bochdalek hernia with the left kidney, adrenal gland, transverse colon, splenic flexure and proximal descending colon within the thorax. The patient underwent elective diagnostic laparoscopy followed by reduction of the contents and mesh repair of the diaphragmatic defect. The patient was discharged and remained asymptomatic on a periodic follow-up of over a year. Awareness regarding this rare entity can obviate the need for a battery of unnecessary investigations and operative procedures.